2011
DOI: 10.1200/jco.2010.29.7614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Prognosis After Early-Stage Breast Cancer

Abstract: Obesity is an independent prognostic factor for developing distant metastases and for death as a result of breast cancer; the effects of adjuvant therapy seem to be lost more rapidly in patients with breast cancer and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
380
3
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 521 publications
(420 citation statements)
references
References 15 publications
28
380
3
9
Order By: Relevance
“…Our results revealed that obesity is associated with larger tumor size and higher tumor grade in both premenopausal and postmenopausal women. These findings are consistent with studies conducted on African American (Zhu et al, 2005), Danish (Ewertz et al, 2011), Iranian (Kaviani et al, 2013) and Asian women (Amadou et al, 2013). However, an inverse association between BMI and BC risk, with a 7% reduction in risk per 5 kg m -2 increase in BMI was documented in premenopausal Caucasians womens (Renehan et al, 2008;Amadou et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Our results revealed that obesity is associated with larger tumor size and higher tumor grade in both premenopausal and postmenopausal women. These findings are consistent with studies conducted on African American (Zhu et al, 2005), Danish (Ewertz et al, 2011), Iranian (Kaviani et al, 2013) and Asian women (Amadou et al, 2013). However, an inverse association between BMI and BC risk, with a 7% reduction in risk per 5 kg m -2 increase in BMI was documented in premenopausal Caucasians womens (Renehan et al, 2008;Amadou et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The relationship between nutritional status and quality of life in patients with cancer has been indicated (Nourissat et al, 2008). The contribution of obesity to risk of breast cancer recurrence has been revealed in several studies (McTiernan, 2005;Toles et al, 2008;Ewertz et al, 2011). It was also related to poor physical performance and quality of life in breast cancer survivors (Elme et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…62 (64%), suffered from a neoplasm belonging to the group of cancers related to obesity, such as colorectal, breast, uterine, ovarian, and kidney cancer. Obesity is a factor associated with the risk of occurrence of multiple malignancies (1, 2, 13-15) and the risk of developing metastases in the course of some malignancies (3,16). However, a favorable influence of overweight and obesity on the course of some neoplastic diseases have been also observed (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%